PENGARUH RASIO PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI - Rahayu, Asti; Mahirun, Mahirun (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of profitability and liquidity ratios on company value with capital structure as a moderating variable. The research method used is a quantitative approach of 13 companies in the food and beverage sector listed on the Indonesia Stock Exchange during the period from 2021 to 2023, while data analysis techniques use Partial Least Square (PLS) approach assisted by Smart-PLS 3.0 software. The results of the study indicate that Return on Assets (RoA) has a positive but insignificant effect on PBV. Similarly, the Current Ratio (CR) and Debt to Equity Ratio (DER) each show a negative effect on PBV, but also have no significant impact. Furthermore, DER as a moderating variable does not strengthen or weaken the relationship between profitability and liquidity ratios and PBV. Overall, these findings suggest that these financial ratios do not significantly affect the company value in the food and beverage sector, and the market is more influenced by other external factors in assessing company value. These results imply that financial ratio information alone is not enough to signal investors in making investment decisions that significantly impact company value in this sector.